Information and communication technology (ICT) based on SPM syllabus - Ahmad, Ibrahim; Zakaria, Mohd Hafiz; Mohammed, Norazlin; Azman, Farah Nadia; Salam, Sazilah; Romli, Rusnida; Mat Sah, Shahrul Badariah; Abdullah, Mohd Haziq Lim (Venton Publishing (M) Sdn Bhd, 2007)
None